Dietary Determinants of Stunting and Underweight in Under-Five Years Children in Pengasinan Health Center's (Puskesmas) Working Area, Depok, West Java - Muthia Syifa Rahmadina; Ratih Qamara Dewi; Arif Hidayat; Satria Yudistira; Fadila Wirawan (Faculty of Public Health Universitas Indonesia, 2023)
Stunting and underweight are public health problems especially in under-five children. This study aims to explore the dietary determinants of stunting and underweight. Participants were 52 under-five children who visited Posyandu in Pengasinan and Bedahan, Depok. Body weight for age z-score (WAZ) and height for age z-score (HAZ) were measured with standardized measurement tools by trained operators. Questionnaires were administered to determine sociodemographic, maternal and child health history, sanitation, disease history, and exclusive breastfeeding history. Data on food intake was obtained through the semi-quantitative Food Frequency Questionnaire and 24-hour recall. There was significant correlation between mother’s income with underweight (P=0.01) and milk consumption’s frequency with protein adecuacy (P=0.01 r=0.44) and calcium adequacy (P=0.00 r=0.74). There was a tendency of correlation between children’s zinc intake (P=0.06) and fat intake (P=0.06) with underweight, and milk consumption’s frequency with HAZ (P=0.05 r=0.28) and WAZ (P=0.07 r=0.25). The frequency of sweetened condensed milk consumption was inversely correlated with HAZ (P=0.01 r=-0.34) and WAZ (P=0.01 r=-0.38). Dietary intake and complimentary beverages affect the nutritional status of a child. Sweetened condensed milk consumption did not support child’s growth. Education about children's nutritional status and complimentary beverage consumption is necessary for mothers, mothers’ support system, and cadres.